15N fertilizer recovery and partitioning by cover crops under greenhouse conditions. (1st November 2020) - Greub, Kelsey L. H.; Roberts, Trenton L.
Abstract: Cover crops have the potential to decrease residual‐nitrogen (N) losses from agricultural soils by capturing and storing excess N between cash crops. This study was established to assess the effect of cover crop species and N rate on the accumulation and partitioning of biomass and 15 N fertilizer by cover crops produced under controlled environmental conditions. Cereal rye ( Secale cereale ) and tillage radish ( Raphanus sativus ) cover crops were grown in monoculture and in a blend under greenhouse conditions in two soils. Urea enriched with 15 N (3.0 atom %) was applied to cover crops at rates of 0, 34, and 67 kg N ha −1 . Shoot dry matter production and N accumulation exceeded that of roots for both cover crops. Fertilizer‐N uptake increased as application rate increased, and the greatest overall recovery by the cover crops was 38% of the applied fertilizer‐N. Tillage radish shoot biomass nearly doubled that of cereal rye (1, 585 kg ha −1 ) when grown in monoculture in the Captina soil but cover crops stored similar quantities of total N in the shoots. Cover crops grown in monoculture in the Roxanna soil accumulated similar amounts of biomass and TN in the shoots; however, cereal rye root biomass was twice that of tillage radish (568 kg ha −1 ) when 67 kg N ha −1 was applied. Results from this study reflect the capacity for N sequestration by cover crops, which is largely determined by biomass production and N availability, and most of the captured N is translocated and stored in the shoots.